The application of Tong-fu therapeutic method on ulcerative colitis: A systematic review and meta-analysis for efficacy and safety of rhubarb-based therapy - Li, Yuzheng; Ye, Zhen; He, Haiqing; Hu, Yu; Wu, Mingquan; Li, Linzhen; Chen, Liulin; Qian, Huanzhu; Shi, Qingyu; Zhang, Chen; Yu, Han; Zhao, Qian; et al. (Frontiers in Pharmacology, 2022)
Background: Tong-fu therapeutic method (TFTM) is a traditional Chinese medicine treatment method for ulcerative colitis, which is a novel treatment strategies and have purgative effect. As the most representative medicinal of TFTM, Rhubarb has been reported to have a therapeutic impact on ulcerative colitis by regulating intestinal flora, anti-inflammation, and improving intestinal microcirculation. Although rhubarb has been widely used in Chinese medicine for the treatment of ulcerative colitis, the appropriate protocol is still demanded to its rational use in clinic, which promoted to evaluate the efficacy and safety for rhubarb-based therapy on ulcerative colitis. Method: Clinical trials were searched through PubMed, Cochrane Library, Web of Science, Excerpta Medica Database, Chinese National Knowledge Infrastructure, WAN FANG Database, Chinese Scientific Journal Database, and Chinese Biomedical Literature Database. The subgroup analyses were performed with three groups: medication, course of treatment, and route of administration. The statistical analyses were performed on Review Manager software (version 5.4.1). Results: A total of 2, 475 patients in 30 original studies were analyzed in this article. It was found that rhubarb-based therapy could increase clinical efficacy and reduce the recurrence rate. Subgroup analyses showed that rhubarb-based therapy was more effective than 5-aminosalicylic acid or sulfasalazine alone. In addition, the hypercoagulable state of ulcerative colitis could be ameliorated by decreasing platelet (PLT) and fibrinogen (FIB), and increasing prothrombin time (PT) significantly. Moreover, C-reaction protein (CRP), tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL-8, and IL-1β expression were significantly reduced, while IL-10 production was increased, which mediated the alleviation of intestinal inflammation stress. Conclusions: Rhubarb-based therapy could effectively improve ulcerative colitis. Of note, the rhubarb-based medicinal formulas combined with 5-ASA or SASP are more effective than the 5-ASA or SASP alone. In addition, although rhubarb has side effect, the results of our analysis showed that rhubarb-based therapy did not exhibit significant side effects. This means it has a high safety profile in clinical use. Moreover, the use of rhubarb-based therapy is recommend to use within 1-13 weeks or 3 months via administered orally or by enema, which is contributes to ensure the curative effect and avoid its toxic and side effects.